Exploring caregivers' experiences of communication with persons with dementia in relation to therapeutic caregiver singing - Stuart-Röhm, Karyn Lesley (University of Pretoria, 2022)
Dissertation (MMus (Music Therapy))--University of Pretoria, 2021.